DDRE-10. IMMUNE PROFILES ASSOCIATE WITH OUTCOMES IN HLA-A*02:01(+), H3.3K27M(+) PATIENTS WITH DIFFUSE MIDLINE GLIOMAS TREATED WITH H3.3K27M PEPTIDE VACCINE COMBINED WITH POLY-ICLC: A PNOC REPORT - Mueller, Sabine (Neuro Oncol, 2020)
BACKGROUND: Patients with diffuse midline gliomas (DMG), including diffuse intrinsic pontine glioma (DIPG), have dismal outcomes. We previously described the H3.3K27M mutation as a shared neoantigen in HLA-A*02.01(+) H3.3K27M(+) DMGs. Within the Pacific Pediatric Neuro-Oncology Consortium, we assessed the safety and efficacy of an H3.3K27M-targeted peptide vaccine. PATIENTS AND METHODS: Newly diagnosed patients aged 3–21 years with positive HLA-A*02.01(+) and H3.3K27M(+) status were enrolled into two strata after completion of radiation therapy: Stratum A for DIPG (n=19); Stratum B for non-pontine DMG (n=10). Vaccine was administered in combination with poly-ICLC every three weeks for eight cycles, followed by once every six weeks. Immunological responses were assessed in peripheral blood mononuclear cells using mass cytometry. RESULTS: 19 patients enrolled in Stratum A (median age=11 years) and 10 in Stratum B (median age=13 years). There were no grade 4 treatment-related adverse events (TRAE). Injection site reaction was the most commonly reported TRAE. Overall survival (OS) at 12 months was 40% (95% CI, 22% to 73%) for Stratum A and 39% (95% CI, 16% to 93%) for Stratum B. The median OS was 16.1 months in patients exhibiting an expansion of H3.3K27M-reactive CD8(+) T-cells compared to 9.8 months for their counterparts (p=0.05). DIPG patients with below-median baseline levels of myeloid-derived suppressor cells had prolonged OS compared to their counterparts (p< 0.1). Immediate pre-treatment dexamethasone administration inversely associated with H3.3K27M-reactive CD8(+) T-cell responses. However, neither tumor size or bulk CD8(+) T-cell status was significantly associated with OS. CONCLUSION: Administration of the H3.3K27M-specific vaccine is well tolerated. Patients with H3.3K27M-specific CD8(+) immunological responses demonstrated prolonged OS compared to non-responders.